A photographic type catalogue of Platygastroidea (Insecta, Hymenoptera) in the Natural History Museum Vienna - Awad, Jessica; Zimmermann, Dominique; Talamas, Elijah (European Journal of Taxonomy, 2024)
As insect decline threatens the fauna of Central Europe, “dark taxa” present an obstacle to understanding biodiversity loss. The superfamily Platygastroidea is a dark taxon, with many superficial descriptions requiring examination of type material to characterize and revise species and genera. The Natural History Museum Vienna (Naturhistorisches Museum Wien) is arguably the most important historical collection of Platygastroidea in Central Europe. Type specimens from 85 species in 21 genera and three families are here catalogued and photographically illustrated, including previously undocumented types described by Förster, Kieffer, Nees von Esenbeck, and Ratzeburg. Lectotypes are designated for Anteris bicolor Kieffer, Anteris simulans Kieffer, Hadronotus laticeps Kieffer, Leptacis foersteri Kieffer, Plastogryon investis Kieffer, Plastogryon sagax Kieffer, Prophanurus mayri Kieffer, and Telenomus laeviceps Förster. Trissolcus schimitsheki (Szelényi) syn. nov. is treated as a junior synonym of Trissolcus scutellaris (Thomson) and Telenomus nomas Förster syn. nov. is treated as a junior synonym of Trissolcus semistriatus (Nees). Baeus maculatus (Förster) comb. nov. is transferred from Telenomus. Historical, taxonomic, and curatorial remarks are included, providing an essential foundation for revisionary work on the Platygastroidea of Central Europe and beyond.